2013
DOI: 10.1158/1055-9965.epi-13-0316-t
|View full text |Cite
|
Sign up to set email alerts
|

Increased Rate of Phenocopies in All Age Groups in BRCA1/BRCA2 Mutation Kindred, but Increased Prospective Breast Cancer Risk Is Confined to BRCA2 Mutation Carriers

Abstract: Background: To establish, if among unaffected noncarrier relatives in a family with an established BRCA1/2 mutation, there is an increased risk of breast cancer.Methods: We identified 49 women with breast cancer who were first-degree relatives of a pathogenic mutation carrier among 807 BRCA1/2 families but who tested negative for the specific mutation. A prospective analysis of breast cancer from date of family ascertainment was performed for first-degree relatives of proven BRCA1/2 mutation carriers and compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Some authors have demonstrated that women who come from BRCA1/2 positive families who themselves test negative for a BRCA gene mutation develop breast cancer at a higher rate than expected. (4951) It has been hypothesized that there are inherited genetic modifiers in these families that increase the risk of breast cancer even in the absence of a deleterious BRCA mutation. It stands to reason that the same could be true for ovarian reserve.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have demonstrated that women who come from BRCA1/2 positive families who themselves test negative for a BRCA gene mutation develop breast cancer at a higher rate than expected. (4951) It has been hypothesized that there are inherited genetic modifiers in these families that increase the risk of breast cancer even in the absence of a deleterious BRCA mutation. It stands to reason that the same could be true for ovarian reserve.…”
Section: Discussionmentioning
confidence: 99%
“…152 Increased risk was seen especially in BRCA2 families with high incidence of breast cancer (Manchester BRCA2 score of > 10), potentially implicating unlinked genetic modifiers causing this excess. Genotyping of 18 breast cancer susceptibility SNPs defined a RR of 1.31 for BRCA2 breast cancer phenocopies with a breast cancer diagnosis aged < 60 years.…”
Section: Study 3: Phenocopiesmentioning
confidence: 99%
“…The identification of path_BRCA1 or path_BRCA2 in an affected BC individual enables access to evidence-based screening for family members, and thus facilitates the implementation of appropriate cancer prevention in these families [ 1 , 5 , 6 ]. However, some women in families with an identified pathogenic variant will develop cancer despite testing negative for the family’s pathogenic variant, often denoted as phenocopies [ 8 ]. In BC kindreds having a demonstrated path_BRCA2 variant, the number of phenocopies is reportedly more frequent than expected by chance [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%